PENGARUH MODEL GAME BASED LEARNING BERBANTUAN WEBSITE ZEP QUIZ TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMK - Tari Rizliyanti; Elfira Rahmadani (Universitas Islam Sumatera Utara, 2026)
The purpose of this study is to determine whether the implementation of the Game Based Learning model assisted by the Zep Quiz website has an effect on the mathematical communication skills of 10th-grade students at SMK Negeri 1 Air Putih in the statistics curriculum for the 2025/2026 academic year. This study is a quasi-experimental study using a two-group Pretest-posttest design. The population in this study consists of all 10th-grade classes, totaling 2 classes. The sample comprises 2 classes. In Class X-RPL 2, the experimental group used the Game-Based Learning model assisted by the Zep Quiz website, while Class X-RPL 1 served as the control group using the expository learning model. After the instruction was completed, posttests were administered, yielding an average score of 80 for the experimental class and 71 for the control class. The results of the t-test showed t_hitung=3,616>t_tabel=1,994; therefore, H₀ is rejected and H_a is accepted. Thus, it was concluded that the mathematical communication skills of students using the Game-Based Learning model assisted by the Zep Quiz website were better than the mathematical communication skills of students using the expository learning model in Grade X at SMK Negeri 1 Air Putih.